Increase in ultrasonic intensity of blood speckle across moderate coronary artery stenosis is an independent predictor of functional coronary artery stenosis measured by fractional flow reserve: pilot study. - Jun Tanno; Shintaro Nakano; Takatoshi Kasai; Junya Ako; Sunao Nakamura; Takaaki Senbonmatsu; Shigeyuki Nishimura (PLoS ONE, 2015)
BACKGROUND AND AIMS:The degree of coronary artery stenosis should be assessed both anatomically and functionally. We observed that the intensity of blood speckle (IBS) on intravascular ultrasound (IVUS) is low proximal to a coronary artery stenosis, and high distal to the stenosis. We defined step-up IBS as the distal minus the proximal IBS, and speculated that this new parameter could be used for the functional evaluation of stenosis on IVUS. The aims of this study were to assess the relationships between step-up IBS and factors that affect coronary blood flow, and between step-up IBS and fractional flow reserve (FFR). METHODS AND RESULTS:This study enrolled 36 consecutive patients with angina who had a single moderate stenosis in the left anterior descending artery. All patients were evaluated by integrated backscatter IVUS and intracoronary pressure measurements. FFR was calculated from measurements using a coronary pressure wire during hyperemia. Conventional gray-scale IVUS images were recorded, and integrated backscatter was measured in three cross-sectional slices proximal and distal to the stenosis. Step-up IBS was calculated as (mean distal integrated backscatter value) - (mean proximal integrated backscatter value). Stepwise multiple linear regression analysis showed that the heart rate (r = 0.45, P = 0.005), ejection fraction (r = -0.39, P = 0.01), and hemoglobin level (r = -0.32, P = 0.04) were independently correlated with step-up IBS, whereas proximal and distal IBS were not associated with these factors. There was a strong inverse correlation between step-up IBS and FFR (r = -0.84, P < 0.001), which remained significant on stepwise multiple linear regression analysis. CONCLUSIONS:The newly defined parameter of step-up IBS is potentially useful for the functional assessment of coronary artery stenosis.